The vegetarian who could not sleep: a case report - Sumathipala, Sanjeewa (International Journal of Research in Medical Sciences, 2020)
Sleep disorders are not unusual presentations to family medicine clinicians. Similarly, patients may have diets that can render them susceptible to vitamin deficiencies. Although not a commonly considered risk factor for sleep disorders, vitamin B12 is involved in the production of melatonin, a hormone regulating the sleep-wake cycle, and supplementation of vitamin B12 has been used to treat sleep disorders. This case study described a patient who presented with a sleep disorder and who was a vegetarian. Although he lacked obvious manifestations of vitamin B12 deficiency, his serum level was almost half the lower limit of normal, and with vitamin B12 supplementation, his sleep improved.